Rasio Keuangan, Laporan Keuangan THE USE OF FINANCIAL RATIOS AS A MEASURING TOOL FOR THE FINANCIAL PERFORMANCE OF BUMDES TO IMPROVE THE WELFARE OF THE PEOPLE OF SIDAYU DISTRICT, GRESIK REGENCY: BUMDES Financial Performance Measurement Strategy Using Financial Ratios - Djulaeka; KHUMAIRO, DURRO; Zulkufli , Makhmud (Universitas Islam Lamongan, 2023)
Sidayu District, as one of the areas in Gresik Regency, has unique characteristics and potential resources that can be developed to realize better economic growth and community welfare. One of the instruments that can be used to optimize this potential is Village-Owned Enterprises (BUMDes). The BUMDes that are the object of this study are BUMDesa Podho Joyo Sukorejo village. In optimizing the role of BUMDes, financial performance evaluation is very necessary to measure financial performance and to encourage the improvement of the welfare of the people of Sidayu District. This study uses descriptive quantitative research methods using a financial ratio analysis approach.The research data used are primary data and secondary data. The results showed that in 2018-2022 the liquidity ratio showed a very poor category. Similarly, the solvency ratio is still said to be very unfavorable due to the increasing debt to total asset ratio and debt to equity ratio. The profitability ratio is said to be sufficient and very good, because the higher the ratio value, the better the financial performance condition of BUMDes. However, in contrast to the activity ratio, BUMDes do not meet the standard for calculating total asset turnover so that they are included in the very poor category.